Cattle feeding hedging and cash margin analysis - Ramey, Holden Milller, author; Koontz, Stephen R., advisor; Frasier, W. Marshall, committee member; Wagner, John J., committee member (Colorado State University. Libraries, 2022)
Historical cattle feeding margins offered through multiproduct hedging, single commodity hedging, and cash markets are determined and compared. Expected margins result from hedging in the commodity futures markets, while actual margins are garnered in the cash market. Price and production data are used to construct a cattle feeding scenario representative of a typical U.S. cattle feeder. Margin equations that account for price, weight, and costs of feeding cattle are developed and adapted to accommodate each type of margin. Actual costs from feedlot closeout data are applied in margin calculations and are also used to construct a model to estimate costs not yet known. Commodity futures are adjusted using both actual and expected methods of basis. This research's primary objective is to determine the mean and risk associated with expected margins generated by hedging strategies and cash margins. Furthermore, insight is acquired on margin opportunities offered by cash and commodity futures markets. Results obtained by this research will be analyzed primarily, using the mean-variance framework. Also, the distribution of expected and actual margins was evaluated and discussed. This study provided a necessary update to research that had previously been done analyzing cattle feeding margins. The goal was to benefit individuals involved in the cattle feeding segment and the U.S. beef industry. This work helped provide cattle feeders with the necessary information to improve cattle feeding margins through well-informed risk management decisions. Implementing the right strategy at the right time to secure margins has many important benefits, though the most important one is the financial soundness of cattle feeding entities.
Keywords: commodities; live cattle; cattle feeding; margins; hedging